Pengaruh Promosi Media Sosial dan Word of Mouth terhadap Keputusan Deposan Memilih Deposito Mantap - Aini, Khoirul; Nur'aeni, Nur'aeni; Dimyati, Dadang (Jurnal Dimamu, 2024)
Based on the results of observations and interviews that underlie this research, the fluctuating number of depositors of deposit products is suspected to be influenced by social media promotion and word of mouth at PT Bank Mandiri Taspen KCP Ujung Berung. This study aims to determine the influence of social media promotion and word of mouth on depositors' decisions to choose deposits at PT Bank Mandiri Taspen KCP Ujung Berung, both partially and simultaneously. The subject of this study is the depositors at PT Bank Mandiri Taspen KCP Ujung Berung. The research is quantitative associative in nature, utilizing primary data. Data collection techniques include observation, interviews, literature review, and questionnaires. The sampling technique employed is non-probability sampling with accidental sampling as the method. The population consists of all depositors at PT Bank Mandiri Taspen KCP Ujung Berung, totaling 259 people, with a sample size of 73 people. The data analysis and hypothesis tests used were determination coefficient analysis, multiple regression analysis, multiple correlation analysis, t-test, and F test. The research results show that social media promotion and word of mouth each have a partial impact on depositor decisions, with an influence of 60.3% and 52.8%, respectively. Simultaneously, there is a significant combined effect of 75.8%.